2018
DOI: 10.1159/000489506
|View full text |Cite
|
Sign up to set email alerts
|

The Renin–Angiotensin System, Not the Kinin–Kallikrein System, Affects Post-Exercise Proteinuria

Abstract: Background/Aims: Temporary proteinuria post-exercise is common and is caused predominantly by renal haemodynamic alterations. One reason is up-regulation of angiotensin II (Ang II) due to the reducing effect of angiotensin-converting enzyme (ACE) inhibitors. However, another, ignored, reason could be the kininase effect of ACE inhibition. This study investigated how ACE inhibition reduces post-exercise proteinuria: by either Ang II up-regulation inhibition or bradykinin elevation due to kininase activity inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Reducing glomerular pressure by blocking the RAA (renin–angiotensin–aldosterone) system alleviates proteinuria, and is considered a fundamental part of nephroprotection in nephropathies with proteinuria [26,27]. During exercise, the filtration fraction increases due to a drop in RBF [12,28]. These changes are related to the activation of the sympathetic nervous system and the renin–angiotensin–aldosterone system [12,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing glomerular pressure by blocking the RAA (renin–angiotensin–aldosterone) system alleviates proteinuria, and is considered a fundamental part of nephroprotection in nephropathies with proteinuria [26,27]. During exercise, the filtration fraction increases due to a drop in RBF [12,28]. These changes are related to the activation of the sympathetic nervous system and the renin–angiotensin–aldosterone system [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…During exercise, the filtration fraction increases due to a drop in RBF [12,28]. These changes are related to the activation of the sympathetic nervous system and the renin–angiotensin–aldosterone system [12,28]. Two recent studies have reported that changes in renal hemodynamics can contribute to albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular pressure reduction through RAA system blockade alleviates albuminuria and is considered to exert a nephroprotective critical role in nephropathies with albuminuria . During physical activities, the filtration rate increases at least in part due to alterations in renal blood flow . These modifications are associated with activation of both the sympathetic nervous system and the RAA system .…”
mentioning
confidence: 99%
“…During physical activities, the filtration rate increases at least in part due to alterations in renal blood flow . These modifications are associated with activation of both the sympathetic nervous system and the RAA system . Some data revealed that changes in renal hemodynamics could contribute to albuminuria .…”
mentioning
confidence: 99%
See 1 more Smart Citation